Heterosis studies for seed yield and yield contributing traits in sesame (Sesamum indicum L.): Heterosis studies for seed yield and yield contributing traits in sesame (Sesamum indicum L.) - A S RATHOD; S P POLE; A J SALUNKE; S G DHAWALE (Journal of Oilseeds Research, 2023)
The highest magnitude of significantly positive heterosis over mid parent to the extent of 77.91 per cent and over standard check JLT-408 to the extent of 34.63 per cent was recorded by the cross RT-351 X TMV-4 and the cross RT-346 X PKDS-11 showed heterosis ( 57.01 %) over better parent for seed yield/plant. The best crosses based on heterosis were RT-351 X TMV-4 and RT-346 X THILARANI identified as the best cross combinations for further exploitation.